Major League Baseball and the competition for leisure dollars in America, 1920-1941 - David G. Surdam; Bryce Eldon Kanago; Kenneth H. Brown (Essays in Economic & Business History (EEBH), 2021)
Major League Baseball faced increased competition from radio broadcasts and improvements in motion pictures during the 1920s and 1930s. The "Roaring Twenties" were followed by the Great Depression. As social norms changed, some owners fought for the right to stage home games on Sundays. Owners put an increased emphasis on promoting home runs, eventually allowed radio broadcasts, and added lights to their stadiums. We include variables for these changes, to estimate the effects upon both home attendance and owners' net income between 1920 and 1941. Team performance, home runs, number of Sundays a team had home games, the installation of lighting, and radio broadcasts of games, all raised attendance while increases in the unemployment rate reduced it. Of these, the number of Sundays on which a team had home games, radio broadcasts, and the unemployment rate had no effect on real net income. All the other variables that raised attendance also raised real net income.
Keywords: L83; N82; 330; Major League Baseball; attendance; Great Depression; leisure spending; net income